Nitrogen-containing organic compound, amphiphilic block polymer and application thereof

By designing the copolymerization of hydrophobic D-A AIE monomers with hydrophilic monomers, amphiphilic block copolymers are prepared to form fluorescent nanoparticles with core-shell structures, solving the problems of low encapsulation rate and irregular structure of nanoparticles in the prior art, achieving efficient fluorescence enhancement and stability improvement, and is suitable for applications such as bioimaging.

CN119912443APending Publication Date: 2025-05-02HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411914638.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the preparation of aggregation-induced luminescence (AIE) nanoparticles, the encapsulation rate is low, the load is low, the use process is prone to sudden release, and the structure is irregular, making it difficult to control performance.

Method used

By combining naphthimide as an electron acceptor with electron donors such as phenothiazine, hydrophobic D-A AIE monomer was designed, and copolymerized with hydrophilic monomer polyethylene glycol monomethyl ether methacrylate by reversible addition-break chain transfer polymerization (RAFT) method to prepare amphiphilic block copolymers to form fluorescent polymer nanoparticles with core-shell structures.

Benefits of technology

It has achieved high encapsulation rate and good stability, with regular structure, good controllability, significant fluorescence enhancement effect, and is suitable for bioimaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912443A_ABST
    Figure CN119912443A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of luminescent materials, in particular to a nitrogen-containing organic compound, an amphiphilic block polymer and application of the nitrogen-containing organic compound and the amphiphilic block polymer. The nitrogen-containing organic compound has a structure as shown in a formula (I). According to the polymer nanoparticles obtained by the invention, a target group is connected to a hydrophobic chain segment of an amphiphilic block polymer through a chemical covalent bond, and the hydrophobic part can automatically gather in an aqueous solution to form micelles. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of luminescent materials, and in particular to nitrogen-containing organic compounds and amphiphilic block polymers and applications thereof. Background Art

[0002] Polymers (possibly conjugated) contain fluorophores, which endow the final material with photoluminescent properties, providing tunable structures, robust mechanical properties, and low detection limits in sensing applications compared to small molecules or inorganic luminescent materials. Among the latter, aggregation-induced emission (AIE) polymers use a novel fluorescence mode that depends on the aggregation state.

[0003] The intramolecular and intermolecular interactions of AIE polymers impart synergistic effects, improving their properties and performance relative to small molecule aggregation-induced, emission-based fluorescent materials. AIE polymers have outstanding advantages such as high emission efficiency, signal amplification, good processability, and multifunctionality.

[0004] As we all know, the physical encapsulation method using non-covalent interaction is simple in preparation; however, the nanoparticles prepared by this method have low encapsulation efficiency, low loading capacity, and are prone to sudden release during use. The AIE fluorescent group is connected to the hydrophobic segment of the amphiphilic polymer through a chemical covalent bond, and the hydrophobic part will automatically aggregate to form micelles in the aqueous solution; the prepared nanoparticles have high encapsulation efficiency and good stability, and their loading capacity can be regulated by adjusting the structure of the polymer.

[0005] In addition, the nanoparticles prepared by the chemical covalent bond method have a regular structure and good controllability, making it easy to establish the relationship between structure and performance, which can provide experimental basis and theoretical foundation for the preparation of fluorescent materials with excellent performance. Summary of the invention

[0006] The purpose of the present invention is to provide a new type of nitrogen-containing organic compound with aggregation-induced delayed fluorescence properties.

[0007] In order to achieve the above-mentioned purpose, the present invention firstly uses naphthylimide as an electron acceptor and one of phenothiazine or phenoxazine or carbazole or 9,9-dimethylacridine or 9,9-diphenylacridine and its derivatives as an electron donor, designs and synthesizes a hydrophobic DA type aggregation-induced fluorescence (AIE) monomer, and then reversibly adds and breaks the chain transfer polymerization (RAFT) with a hydrophilic monomer polyethylene glycol monomethyl ether methacrylate and its homologues, polyethylene glycol monomethyl ether acrylate and one of its homologues to obtain an AB type amphiphilic fluorescent block copolymer with different hydrophilic and hydrophobic ratios.

[0008] Specifically, the present invention provides a nitrogen-containing organic compound having a structure shown in formula (I):

[0009]

[0010] Wherein, in formula (I),

[0011] L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving;

[0012] R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxyl groups;

[0013] X is S, O or -C(R 51 R 52 )-, R 51 , R 52 Each independently selected from C 1-6 or X does not exist so that the two phenyl groups are directly bonded.

[0014] The second aspect of the present invention provides an amphiphilic block polymer, which contains an A structural unit and a B structural unit; the A structural unit is a structural unit provided by at least one of the nitrogen-containing organic compounds described in the first aspect, and the B structural unit is a structural unit provided by a hydrophilic compound.

[0015] The third aspect of the present invention provides use of the nitrogen-containing organic compound described in the first aspect and / or the amphiphilic block polymer described in the second aspect in an aggregation-induced emission material.

[0016] The fourth aspect of the present invention provides use of the amphiphilic block polymer described in the second aspect in biological imaging.

[0017] The amphiphilic block polymer of the present invention forms micellar nanoparticles through self-assembly, the hydrophilic group encapsulates the hydrophobic fluorescent group, the aggregation of the fluorescent group realizes the fluorescence enhancement of the nanoparticles, exhibits the property of aggregation-induced luminescence, and can be applied to the field of biological imaging.

[0018] The invention firstly uses naphthylimide as an electron acceptor and one of phenothiazine or phenoxazine or carbazole or 9,9-dimethylacridine or 9,9-diphenylacridine and derivatives thereof as an electron donor, designs and synthesizes a hydrophobic DA type aggregation-induced fluorescence (AIE) monomer, and then performs reversible addition-fragmentation chain transfer polymerization with hydrophilic monomers such as polyethylene glycol monomethyl ether methacrylate and its homologues and polyethylene glycol monomethyl ether acrylate and its homologues to obtain AB type amphiphilic fluorescent block copolymers with different hydrophilic and hydrophobic ratios.

[0019] The polymer nanoparticles obtained by the present invention are obtained by connecting the fluorescent group to the hydrophobic segment of the amphiphilic block polymer through a chemical covalent bond, and in an aqueous solution, micellar nanoparticles are formed by self-assembly; the hydrophilic group encapsulates the hydrophobic fluorescent group, and the aggregation of the fluorescent group realizes the fluorescence enhancement of the nanoparticles. In addition, the nanoparticles of the present invention have a regular structure and good controllability, and it is easy to establish the relationship between the structure and the performance, which can provide an experimental basis and a theoretical basis for the preparation of fluorescent materials with excellent performance.

[0020] The amphiphilic aggregation-induced fluorescent block copolymer of the invention is used to prepare fluorescent polymer nanoparticles with a core-shell structure through self-assembly. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the synthetic route for preparing the amphiphilic block polymer in Example 1.

[0022] Figure 2 is the nuclear magnetic resonance (NMR) of the macromolecular chain transfer agent POEGMA-CTA prepared in Example 1 1 H NMR) spectrum.

[0023] Figure 3 is the NMR of the amphiphilic block polymer prepared in Example 1 ( 1 H NMR) spectrum.

[0024] Figure 4 This is the gel permeation chromatography (GPC) spectrum of the amphiphilic block polymer prepared in Example 1.

[0025] Figure 5 This is the photoluminescence spectrum of the amphiphilic block polymer prepared in Example 1 in a DCM / n-hexane system.

[0026] Figure 6 This is a dynamic light scattering (DLS) particle size distribution diagram of the micellar nanoparticles of the amphiphilic block polymer prepared in Example 1 in aqueous solution.

[0027] Figure 7This is a transmission electron microscopy (TEM) image of the self-assembly morphology of the amphiphilic block polymer prepared in Example 1 in aqueous solution. DETAILED DESCRIPTION

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] “C 1-6 The term "alkyl" refers to an alkyl group having 1 to 6 carbon atoms, including straight-chain alkyl groups and branched-chain alkyl groups, for example, straight-chain alkyl groups and branched-chain alkyl groups having 1, 2, 3, 4, 5, or 6 carbon atoms, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, etc.

[0030] “C 1-6 The "alkoxy group" refers to an alkoxy group having a total of 1 to 6 carbon atoms, including straight-chain alkoxy groups and branched-chain alkoxy groups, for example, straight-chain alkoxy groups and branched-chain alkoxy groups having a total of 1, 2, 3, 4, 5, or 6 carbon atoms, for example, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentyloxy, n-hexyloxy, and the like.

[0031] As mentioned above, the first aspect of the present invention provides a nitrogen-containing organic compound having a structure shown in formula (I); wherein, in formula (I),

[0032] L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving;

[0033] R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxyl groups;

[0034] X is S, O or -C(R 51 R 52 )-,R 51, R 52 Each independently selected from C 1-6 or X does not exist so that the two phenyl groups are directly bonded.

[0035] According to a preferred embodiment, in formula (I),

[0036] L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving;

[0037] R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each independently selected from H, C 1-4 Alkyl, C 1-4 Alkoxyl groups;

[0038] X is S, O or -C(R 51 R 52 )-, R 51 , R 52 Each independently selected from C 1-4 or X does not exist so that the two phenyl groups are directly bonded.

[0039] According to another preferred embodiment, in formula (I),

[0040] L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving;

[0041] R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each is independently selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy;

[0042] X is S, O or -C(R 51 R 52 )-, R 51 , R52 Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl; or X is absent so that the two phenyl groups are directly bonded.

[0043] According to a particularly preferred embodiment, the structure shown in formula (I) is selected from any one of the following:

[0044]

[0045]

[0046] The present invention has no particular limitation on the specific method for preparing the aforementioned nitrogen-containing organic matter. A person skilled in the art can obtain the aforementioned nitrogen-containing organic matter of the present invention according to the specific structural formula provided by the present invention in combination with the known knowledge in the field of synthesis. In addition, several examples are exemplarily listed in the following text of the present invention to illustrate the preparation method of the nitrogen-containing organic matter of the present invention. A person skilled in the art can also obtain the specific preparation method of all other nitrogen-containing organic matters by replacing the type of raw materials according to the preparation method of the nitrogen-containing organic matter in the following text of the present invention. The present invention will no longer describe in detail the preparation methods of all nitrogen-containing organic matters, and a person skilled in the art should not interpret this as a limitation of the present invention.

[0047] As mentioned above, the second aspect of the present invention provides an amphiphilic block polymer, which contains an A structural unit and a B structural unit; the A structural unit is a structural unit provided by at least one of the nitrogen-containing organic compounds described in the first aspect, and the B structural unit is a structural unit provided by a hydrophilic compound.

[0048] Preferably, the hydrophilic compound is selected from at least one of polyethylene glycol monomethyl ether methacrylate and its homologues, polyethylene glycol monomethyl ether acrylate and its homologues.

[0049] According to a particularly preferred embodiment, the hydrophilic compound is polyethylene glycol monomethyl ether polymethacrylate, and the compound has the structure shown below:

[0050]

[0051] Preferably, the molar ratio of the A structural unit to the B structural unit is 1:0.001-1000.

[0052] Preferably, the weight average molecular weight of the amphiphilic block polymer is 500 to 500,000.

[0053] According to a particularly preferred embodiment, the amphiphilic block polymer is selected from any one of the following, and each x, each y, each m, and each n are each independently selected from a positive integer of 1-1000; more preferably, each x, each y, each m, and each n are each independently selected from a positive integer of 1-300:

[0054]

[0055] The present invention has no particular restrictions on the specific method for preparing the aforementioned amphiphilic block polymer. Those skilled in the art can obtain the aforementioned amphiphilic block polymer of the present invention according to the structural formula in combination with known knowledge in the field of synthesis (or polymerization), and the present invention hereinafter exemplarily lists several examples to illustrate the preparation method of the amphiphilic block polymer of the present invention. Those skilled in the art can also obtain the specific preparation method of all other amphiphilic block polymers by replacing the type of raw materials according to the preparation method of the amphiphilic block polymer in the following text of the present invention. The present invention no longer describes in detail the preparation methods of all amphiphilic block polymers, and those skilled in the art should not be construed as limiting the present invention.

[0056] As mentioned above, the third aspect of the present invention provides the use of the nitrogen-containing organic compound described in the first aspect and the amphiphilic block polymer described in the second aspect in aggregation-induced emission materials.

[0057] As mentioned above, the fourth aspect of the present invention provides the use of the amphiphilic block polymer described in the third aspect in biological imaging.

[0058] The amphiphilic block polymer of the present invention forms micellar nanoparticles through self-assembly, the hydrophilic group encapsulates the hydrophobic fluorescent group, the aggregation of the fluorescent group realizes the fluorescence enhancement of the nanoparticles, exhibits the property of aggregation-induced luminescence, and can be applied to the field of biological imaging.

[0059] The electron acceptor of the hydrophobic AIE group of the amphiphilic block polymer of the present invention is preferably 1,8-naphthalene diimide, and the electron donor is preferably any one of phenothiazine, phenoxazine, carbazole, 9,9-dimethylacridine, 9,9-diphenylacridine and derivatives thereof.

[0060] The hydrophilic segment of the amphiphilic block polymer of the present invention is preferably polyethylene glycol monomethyl ether methacrylate and its homologues, polyethylene glycol monomethyl ether acrylate and its homologues.

[0061] The present invention conducts reversible addition-fragmentation chain transfer polymerization (RAFT) of a hydrophobic AIE monomer (A) and a hydrophilic monomer (B) to obtain the amphiphilic block polymer, which is a novel AB-type amphiphilic aggregation-induced emission block copolymer.

[0062] The amphiphilic block polymer provided by the present invention exhibits aggregation-induced emission (AIE) characteristics in both an aqueous solution system and an organic solvent / n-hexane system.

[0063] The amphiphilic block polymer provided by the invention can prepare fluorescent polymer nanoparticles with a core-shell structure through self-assembly.

[0064] Preferably, the present invention combines naphthalene anhydride (electron acceptor A) with one of phenothiazine or phenoxazine or carbazole, 9,9-dimethylacridine or 9,9-diphenylacridine and derivatives (electron donor D) to design a DA-type fluorescent monomer A with aggregation-induced emission properties, and copolymerizes it with a hydrophilic monomer B by a reversible addition-fragmentation chain transfer polymerization (RAFT) method to obtain a novel amphiphilic AB-type block copolymer with aggregation-induced emission properties. The block copolymer forms nanoparticles by self-assembly in an aqueous solution; the hydrophilic group encapsulates the hydrophobic fluorescent group, and the aggregation of the fluorescent group realizes the fluorescence enhancement of the nanoparticles.

[0065] The amphiphilic block polymer provided by the invention has a fluorescence enhancement effect after self-assembly to form polymer nanoparticles.

[0066] The drugs and reagents used in the following specific examples are all of analytical purity and, unless otherwise specified, can be obtained from commercial sources and used directly without purification.

[0067] Example 1

[0068] This example proposes to use naphthaleneimide as an electron acceptor and phenothiazine as an electron donor to carry out RAFT polymerization with a hydrophobic AIE monomer and a hydrophilic polyethylene glycol monomethyl ether polymethacrylate monomer (OEGMA) to obtain a novel AB type amphiphilic block copolymer, the molecular structure of which is shown below:

[0069]

[0070] Combination Figure 1 This embodiment is further described, and its synthetic route comprises the following steps:

[0071] Step 1: Add 4-bromo-1,8-naphthalene dicarboxylic anhydride (3.61mmol) to a 500ml round-bottom flask, then add 350ml ethanol and stir for 30min. Then dilute ethanolamine (5.41mmol) with ethanol and slowly add it to the round-bottom flask, heat to 80℃, reflux for 16h, and track by TLC until the reaction is complete. After the reaction is complete, dilute the reaction solution with 200ml ethanol, put it in the refrigerator for 4h, filter it, wash the filter cake with ice ethanol (100ml×3), and dry the filter cake in a 40℃ vacuum oven for 12h. A light gray solid is obtained with a yield of 86.5%.

[0072] Step 2: Add N-hydroxyethyl-4-bromo-1,8-naphthalimide (3.12mmol) and p-toluenesulfonic acid monohydrate (3.75mmol) to a 500ml round-bottom flask and stir for 30min to make the two evenly dispersed in dichloromethane. Transfer the reaction to an ice bath, dissolve 3,4-dihydropyran (4.67mmol) in 60ml dichloromethane, and slowly add it to the reaction bottle through a constant pressure dropping funnel. Stir for 15min under ice bath and then transfer to 20℃ for reaction. TLC tracking until the reaction is complete, reaction time 12h. After the reaction is completed, add 200ml of dichloromethane to dilute, and filter the reaction solution. Place the filtrate in a 1000ml separatory funnel, wash three times with water, and wash once with a saturated sodium chloride solution. The organic phase was collected, anhydrous magnesium sulfate was added to the organic phase and dried overnight, filtered, the solvent was dried by spin-drying, and then purified by chromatography column method (the eluent was a mixed solvent of dichloromethane and ethyl acetate in a volume ratio of 20:1, and the first component was collected), the solvent was dried by spin-drying, and the dried solid was placed in a vacuum drying oven at 40°C and vacuum dried to obtain a white solid with a yield of 69.8%.

[0073] Step 3: Add 4-bromo-1,8-naphthaleneimide ethoxypyran (19.79mmol), phenothiazine (21.77mmol), tri-tert-butylphosphine tetrafluoroborate (2.37mmol), palladium acetate (0.99mmol), sodium tert-butoxide (49.48mmol) to a 500ml three-necked flask, and add 360ml toluene. Expel the air in the three-necked flask with nitrogen gas, and allow the reaction to proceed in a nitrogen atmosphere. Stir at room temperature for 30min and then heat to 120℃ for reaction. TCL spot plate tracking allows 4-bromo-1,8-naphthaleneimide ethoxypyran to react completely, the reaction time is 16h, and after the reaction is completed, the toluene is dried, the dried solid is dissolved in dichloromethane, washed three times with water, and washed once with sodium chloride salt. Anhydrous magnesium sulfate was added to the organic phase and dried overnight, filtered, and then purified by chromatography column method (first, pure dichloromethane was used to collect phenothiazine, and then dichloromethane and ethyl acetate were used in a volume ratio of 25:1 to collect the target product), the solvent was dried, and the dried product was placed in a vacuum drying oven at 40°C and dried under vacuum to obtain a red solid with a yield of 63%.

[0074] Step 4: Add 6-(9H-phenothiazine)-1,8-naphthaleneimide ethoxypyran (2.65mmol) and p-toluenesulfonic acid monohydrate (0.52mmol) to a 100ml single-necked bottle and dissolve in a mixed solvent of 12.5ml dichloromethane and 25ml methanol, react at 20℃, track with TCL dot plate, and the reaction time is 2h. After the reaction is completed, the solvent is removed by rotary evaporation, the residue is dissolved in dichloromethane, washed three times with saturated sodium bicarbonate solution, washed once with water, the organic phase is dried with anhydrous magnesium sulfate, filtered, the solvent is dried by rotary evaporation, and the dried solid is placed in a vacuum drying oven at 40℃ for vacuum drying. The dried solid is dissolved in dry dichloromethane and added to a 250ml three-necked bottle, filled with nitrogen under an ice bath, and 0.3ml of dry triethylamine is added. Methacryloyl chloride (0.4g, 0.38mmol) is dissolved in dichloromethane and placed in a constant pressure dropping funnel, and the reaction solution is slowly dripped into it. TCL spot plate tracking, reaction time 45min, after the reaction is complete, add 40ml water to quench the reaction, wash three times with sodium bicarbonate solution, wash once with water, wash once with sodium chloride salt, dry the organic phase with anhydrous magnesium sulfate overnight, filter, spin dry and purify by chromatography column method (eluent is dichloromethane, collect the first component). Spin dry the solvent, put the spin-dried solid into a vacuum drying oven at 40°C and dry it under vacuum to obtain the product as a red solid, yield: 73.2%. The red solid product was characterized, and the results were: 1 H NMR (400MHz, δ, ppm, CDCl3) δ8.83 (d, J = 7.7Hz, 1H), 8.66 (dd, J = 7.3, 1.2Hz, 1H), 8.54 (dd, J = 8. 5,1.2Hz,1H),7.96(d,J=7.7Hz,1H),7.74(dd,J=8.5,7.3Hz,1H),7.09(dd,J=7.6,1.6Hz,2H), 6.85(td,J=7.4,1.3Hz,2H),6.77(ddd,J=8.8,7.3,1.6Hz,2H),6.09(t,J=1.3Hz,1H),6.07-5. 93(m,2H),5.55(p,J=1.6Hz,1H),4.68-4.57(m,2H),4.57-4.46(m,2H),1.91(t,J=1.3Hz,3H). 13 CNMR(101MHz, CDCl3)δ167.32,143.53,136.04,132.25,132.01,131.31,130.41,130.39,130.28 ,128.27,127.11,127.03,126.00,123.38,123.25,122.87,120.52,115.80,62.12,39.16,18.34.

[0075] Step 5: Add ethanethiol (0.04 mol) and potassium phosphate (0.044 mol) to a 250 ml single-mouth bottle, add 100 ml of acetone and stir for 20 min, then add carbon disulfide (0.12 mol), the solution turns yellow and continues to stir for 20 min, finally add methyl 2-bromopropionate (0.044 mol), stir for 15 min, after the reaction is completed, filter the reaction solution, wash the solid with a small amount of acetone, and purify the filtrate by chromatography column method (the volume ratio of the eluent is petroleum ether: ethyl acetate = 5:4, collect the first component). Spin the solvent dry, put it into a 35 ° C vacuum drying oven and vacuum dry to obtain a yellow oily liquid, yield: 69.8%. The yellow oily liquid was characterized, and the results were: 1 H NMR(400MHz,Chloroform-d)δ4.84(qd,J=7.4,1.0Hz,1H),3.75(d,J=1.0Hz,3H),3. 37(qd,J=7.4,0.9Hz,2H), 1.60(dd,J=7.4,0.9Hz,3H), 1.36(td,J=7.4,0.9Hz,3H).

[0076] Step 6: Take a clean and dry ampoule tube, add magnetite, add 2g of OEGMA, 377ul of RAFT agent with a concentration of 0.1g / ml tetrahydrofuran solution, 553μl of AIBN with a concentration of 0.01g / ml tetrahydrofuran solution (the molar ratio of monomer: RAFT agent: initiator is 125:5:1), and 3.74ml of refined tetrahydrofuran (monomer mass concentration is 30%). Use liquid nitrogen to freeze-vacuum-thaw-continue to pass nitrogen, cycle five times, and finally seal the tube under the frozen vacuum state. After sealing, put it in methanol to thaw, and put the ampoule tube into an oil bath at 75℃ for reaction. After reacting for 12h, take out the ampoule tube and quickly put it in ice water to cool and stop polymerization. Open the ampoule tube, add 10ml of tetrahydrofuran to dissolve and dilute the polymer, take out the polymer solution with a 2ml syringe, slowly drip it into a beaker filled with 400ml petroleum ether, the polymer sticks to the bottom of the beaker, pour out the solvent, repeat more than 3 times, until the nuclear magnetic hydrogen spectrum can no longer detect the double bond peak of the monomer, finally transfer the solution dissolved in tetrahydrofuran to a 25ml glass bottle, spin dry the solvent and put it in a 35℃ vacuum drying oven to dry for 24h to obtain a viscous polymer POEGMA-CTA with a yield of 87.1%. Combined with nuclear magnetic hydrogen spectrum and gel permeation chromatography, it can be seen that the number average molecular weight of POEGMA-CTA is 7380, the molecular weight distribution is 1.08, and the number of OEGMA structural units is 15.

[0077] Step 7: Using 6-(9H-phenothiazine)-1,8-naphthylimide ethoxypyranyl methacrylate as AIE monomer, POEGMA-CTA as macromolecular chain transfer agent, and AIBN as initiator, RAFT polymerization was performed to regulate the feed ratio of AIE monomer and macromolecular chain transfer agent POEGMA-CTA (the molar ratio of hydrophilic monomer: fluorescent monomer. That is, the molar ratio of x and y) was 0.1875:1, 0.25:1, 0.375:1, 0.75:1, 1.25:1), respectively, to synthesize five amphiphilic fluorescent block copolymers POEGMA-MANAI-PPTZn with different molecular weights. The synthesis of POEGMA-MANAI-PPTZ12 (molar ratio of x and y is 1.25:1) is taken as an example for detailed introduction. Take a clean and dry ampoule tube, add magnetite, add 0.4g of 6-(9H-phenothiazine)-1,8-naphthylimide ethoxypyranyl methacrylate, 0.28g of macromolecular chain transfer agent POEGMA-CTA, 111μl of AIBN with a concentration of 0.01g / ml tetrahydrofuran solution (the molar ratio of monomer: macromolecular chain transfer agent: initiator is 60:5:1), and 1.4ml of refined tetrahydrofuran (monomer mass concentration is 30%). Use liquid nitrogen to freeze-vacuum-thaw-continue to pass nitrogen, cycle five times, and finally seal the tube under the frozen vacuum state. After sealing, put it in methanol to thaw, and put the ampoule tube into an oil bath at 75℃ for reaction. After 6h of reaction, take out the ampoule tube and quickly put it in ice water to cool and stop polymerization. Open the ampoule tube, add 10 ml of tetrahydrofuran to dissolve and dilute the polymer, take out the polymer solution with a 2 ml syringe, and slowly drip it into a mixed solvent containing 200 ml of acetone and methanol in a volume ratio of 2:1. Stir continuously during the dripping process. The polymer precipitates in this solvent and the monomer dissolves. After the precipitation is completed, the solid polymer is obtained by centrifugation. Repeat this for more than 3 times until the double bond peak of the monomer can no longer be detected by the nuclear magnetic hydrogen spectrum. Finally, the red solid obtained after centrifugation is placed in a 40°C vacuum drying oven and dried for 24 hours to obtain the polymer. Figure 3 The NMR characterization of the polymer is shown.

[0078] Test Example 1

[0079] After obtaining the relevant luminescent fluorescent compounds, their properties are characterized.

[0080] Figure 2 The NMR spectrum of the macromolecular chain transfer agent POEGMA-CTA obtained in Example 1 is shown. From the NMR spectrum, it can be seen that the macromolecular chain transfer agent POEGMA-CTA has been successfully synthesized; the number average molecular weight is 7380, and the number of OEGMA structural units is 15.

[0081] Figure 4The molecular weight and molecular weight distribution of the amphiphilic block copolymer obtained in Example 1 are shown. From the GPC curve, it can be seen that the number average molecular weight of the copolymer is 1.23×10 4 -2.90×10 4 With the increase of hydrophobic fluorescent monomer, the molecular weight increases, and the molecular weight distribution is within 1.34.

[0082] Figure 5 The fluorescence spectra of the amphiphilic block copolymer POEGMA-MANAI-PPTZ12 (molar ratio of hydrophilic monomer: fluorescent monomer, i.e., the molar ratio of x to y is 1.25:1) are shown, wherein (a) represents the fluorescence spectra of the block copolymer in dichloromethane / n-hexane solutions with different amounts of n-hexane; (b) represents the I / I0 relationship curve of the fluorescence spectrum of the block copolymer, where I0 and I are the fluorescence intensities in pure dichloromethane solution and solutions with different dichloromethane / n-hexane volume ratios, respectively. Using dichloromethane as a good solvent and n-hexane as a poor solvent, its aggregation-induced emission properties are characterized. The fluorescence intensity is not high in pure dichloromethane solution. When n-hexane is added, the fluorescence intensity is not high. w =0% and continuously increases, the increase of poor solvent gradually forms molecular aggregates, which greatly limits the restricted intramolecular rotation (RIR), blocks the non-radiative relaxation pathway, and makes the fluorescence enhancement emission intensity continuously increase, f w =95% reached the maximum fluorescence intensity, which increased 495 times compared with its fluorescence intensity in pure dichloromethane, which is a typical aggregation-induced emission phenomenon.

[0083] Figure 6 The dynamic light scattering (DLS) particle size distribution diagram of micellar nanoparticles formed by self-assembly of each amphiphilic block copolymer is shown, wherein (a) represents the amphiphilic fluorescent block copolymer POEGMA-MANAI-PPTZ nDLS particle size distribution of micellar nanoparticles; (b) A graph showing the change in polymer and particle size with different polymerization degrees. In the structure of the amphiphilic fluorescent block copolymer, the hydrophobic AIE monomer constitutes the core of the micellar nanoparticle, and the hydrophilic OEGMA constitutes the shell of the micellar particle. When forming a stable core-shell structure, the self-assembly to form micelles is not affected by the concentration. Even at very low concentrations, the micelles can exist in a stable form, and the size of the micellar particles is not affected by the concentration. The particle size of amphiphilic block copolymers with different polymerization degrees in aqueous solution and the polydispersity (PDI) of the nanoparticles in water were measured by dynamic light scattering (DLS). The particle sizes of the amphiphilic block copolymer micellar nanoparticles were 197.06nm, 202.96nm, 223.61nm, 234.61nm and 266.36nm, respectively, and the PDI was less than 0.08, which was a narrow distribution sample. The relationship diagram of the nanoparticle size of polymers with different polymerization degrees shows that as the number of hydrophobic segments increases, the size of the micelle nanoparticles also increases. This is because as the number of hydrophobic segments increases, the size of the formed inner core increases, and therefore the particle size of the micelle nanoparticles also increases.

[0084] Figure 7 The results of TEM test on micelles are shown, where the left side shows the amphiphilic fluorescent block copolymer POEGMA-MANAI-PPTZ 80 (The molar ratio of hydrophilic monomer: fluorescent monomer, i.e. the molar ratio of x to y is 0.1875:1) TEM image; the right side shows POEGMA-MANAI-PPTZ 12 (The molar ratio of hydrophilic monomer: fluorescent monomer, that is, the molar ratio of x to y is 1.25:1) TEM image of micellar nanoparticles. It can be seen that the amphiphilic aggregation-induced luminescence nanoparticles self-assemble in water to form an irregular vesicle shape with OEGMA as the shell and AIE group as the core. With the increase of hydrophobic segments, a larger core is formed.

[0085] The above results show that the present invention provides a type of DA-type monomer with aggregation-induced emission properties based on naphthalene imide as an acceptor, prepares amphiphilic fluorescent block copolymers through RAFT polymerization, and constructs a series of novel amphiphilic aggregation-induced emission polymer nanoparticle polymer materials. The fluorescent group is connected to the hydrophobic segment of the amphiphilic block polymer through a chemical covalent bond, and the hydrophobic part will automatically aggregate to form micelles in an aqueous solution; the prepared nanoparticles have a regular structure and good controllability, and can be regulated by adjusting the structure of the polymer.

[0086] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A nitrogen-containing organic compound, characterized in that The nitrogen-containing organic compound has a structure shown in formula (I): Wherein, in formula (I), L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving; R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxyl groups; X is S, O or -C(R 51 R 52 )-, R 51 , R 52 Each independently selected from C 1-6 or X does not exist so that the two phenyl groups are directly bonded.

2. The nitrogen-containing organic compound according to claim 1, characterized in that In formula (I), L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving; R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each independently selected from H, C 1-4 Alkyl, C 1-4 Alkoxyl groups; X is S, O or -C(R 51 R 52 )-, R 51 , R 52 Each independently selected from C 1-4 or X does not exist so that the two phenyl groups are directly bonded.

3. The nitrogen-containing organic compound according to claim 2, characterized in that In formula (I), L is present or absent, and the optional L is a linking group formed by benzene leaving any two H capable of leaving; R 11 , R 12 , R 13 , R 31 , R 32 , R 33 , R 34 , R 41 , R 42 , R 43 and R 44 Each is independently selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy; X is S, O or -C(R 51 R 52 )-, R 51 , R 52 Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl; or X is absent so that the two phenyl groups are directly bonded.

4. The nitrogen-containing organic compound according to claim 3, characterized in that The structure shown in formula (I) is selected from any one of the following:

5. An amphiphilic block polymer, characterized in that The amphiphilic block polymer contains A structural units and B structural units; the A structural unit is a structural unit provided by at least one of the nitrogen-containing organic compounds described in any one of claims 1 to 4, and the B structural unit is a structural unit provided by a hydrophilic compound.

6. The amphiphilic block polymer according to claim 5, characterized in that The hydrophilic compound is at least one selected from polyethylene glycol monomethyl ether methacrylate and its homologues, polyethylene glycol monomethyl ether acrylate and its homologues.

7. The amphiphilic block polymer according to claim 5 or 6, characterized in that The molar ratio of the A structural unit to the B structural unit is 1:0.001-1000; Preferably, the weight average molecular weight of the amphiphilic block polymer is 500 to 500,000.

8. The amphiphilic block polymer according to any one of claims 5 to 7, characterized in that The amphiphilic block polymer is selected from any one of the following, and each x, each y, each m, and each n are each independently selected from a positive integer of 1-1000; preferably, each x, each y, each m, and each n are each independently selected from a positive integer of 1-300:

9. Use of the nitrogen-containing organic compound according to any one of claims 1 to 4 and the amphiphilic block polymer according to any one of claims 5 to 8 in aggregation-induced emission materials.

10. Use of the amphiphilic block polymer according to any one of claims 5 to 8 in biological imaging.